2014
DOI: 10.4338/aci-2014-04-ra-0026
|View full text |Cite
|
Sign up to set email alerts
|

Patient No-Show Predictive Model Development using Multiple Data Sources for an Effective Overbooking Approach

Abstract: This paper demonstrates an alternative way to accommodate overbooking, accounting for the prediction of an individual patient's show/no-show status. The predictive no-show model leads to a dynamic overbooking policy that could improve patient waiting, overtime, and total costs in a clinic day while maintaining a full scheduling capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 52 publications
3
51
1
Order By: Relevance
“…Medium-scale studies (ranging from 6,000 to 8,000 patients) focused on a few patient characteristics or a single (eg, time) component. 11 - 13 For example, a large-scale no-show modeling of a Veterans Affairs (VA) outpatient clinic included 555,183 patients, which scheduled 25,050,479 appointments; however, the study only considered a few variables such as the patient gender, the date of the appointment, and new versus established patients. 14 Most studies developed regression models to predict appointment nonadherence.…”
Section: Introductionmentioning
confidence: 99%
“…Medium-scale studies (ranging from 6,000 to 8,000 patients) focused on a few patient characteristics or a single (eg, time) component. 11 - 13 For example, a large-scale no-show modeling of a Veterans Affairs (VA) outpatient clinic included 555,183 patients, which scheduled 25,050,479 appointments; however, the study only considered a few variables such as the patient gender, the date of the appointment, and new versus established patients. 14 Most studies developed regression models to predict appointment nonadherence.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete study rates vary from an average of 2.3% (2) to as high as 25–39% in selected anxious populations, even when larger bore claustrophobia-friendly open scanners are used (3). No-shows and incompletions result in ineffective utilization and financial losses (4, 5). Word of mouth from dissatisfied patients may also potentially dissuade friends and family members as future patients (6, 7).…”
Section: Introductionmentioning
confidence: 99%
“…To ascertain uninterruptible treatment procedures and control for contant workstations, by implementing novel work ows to continue essential treatment planning and delivery in the outpatient and inpatient setting. Underutilizition of medical resources hold negative impacts by increasing healthcare costs, decreasing access to care, and reducing e ciency and productivity of care providers [7]. As the most common reasons for missing medical appointments are forgetting (35.5.%) and miscommunication (31.5%) [35], it is recommended to and proactively schedule patients to diminish negative impacts of patient no-shows [8].…”
Section: Discussionmentioning
confidence: 99%
“…As the most common reasons for missing medical appointments are forgetting (35.5.%) and miscommunication (31.5%) [35], it is recommended to and proactively schedule patients to diminish negative impacts of patient no-shows [8]. While predictive models propose overbooking approaches to signi cantly reduce patient waiting by at least 6%, 27% on overtime, and 3% on total costs compared to at-overbooking methods [7], our Department early focused on controlling appointment compliance while avoiding over-booking. Analysing calender weeks 12-19 of years 2019 and 2020 year-to-date, we found that while reducing the overall number of patients presenting to the Department of Radiation Oncology by 10.3%, the resulting daily number of patients starting radiation therapy was increased by 18.5% (7.5 vs. 8.8; SD 2.93 vs. 0.63) p=0.026 year to date.…”
Section: Discussionmentioning
confidence: 99%